2015
DOI: 10.1080/17451000.2015.1062521
|View full text |Cite
|
Sign up to set email alerts
|

Megafaunal communities along a depth gradient on the tropical Brazilian continental margin

Abstract: The species composition, abundance and diversity patterns of the epibenthic megafauna and fish community from the tropical Brazilian continental margin were analysed based on 42 bottom trawls from the Campos Basin continental shelf and slope. Trawls were collected aboard R/V Gyre during autumn 2008 from depths of 13 to 2030 m. Overall, 452 species belonging to five main taxa were identified: teleosts (Actinopterygii) were represented by 196 species, crustaceans by 113 species and echinoderms by 108 species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…The attributes SL and LD were revealed as very important for the composition of the rules. Those descriptors are directly related to other abiotic (eg, temperature and water salinity) and biotic (food availability) factors that influence the places where these marine beings inhabit [26], [27]. According to [27], depth is the main structuring factor of marine megafauna communities (macroscopic animals).…”
Section: Resultsmentioning
confidence: 99%
“…The attributes SL and LD were revealed as very important for the composition of the rules. Those descriptors are directly related to other abiotic (eg, temperature and water salinity) and biotic (food availability) factors that influence the places where these marine beings inhabit [26], [27]. According to [27], depth is the main structuring factor of marine megafauna communities (macroscopic animals).…”
Section: Resultsmentioning
confidence: 99%
“…Situation 1 can be sustained, as lolignid squids ( Doryteuthis plei and D. sanpaulensis ) have a strong association with the sea bottom and are considered abundant in the inner shelf from 10 to 50 m (Robin et al ., 2014; Costa et al ., 2015). A short distance south (100 km), in the Cabo Frio upwelling region, Soares et al .…”
Section: Discussionmentioning
confidence: 99%
“…Situation 1 can be sustained, as lolignid squids (Doryteuthis plei and D. sanpaulensis) have a strong association with the sea bottom and are considered abundant in the inner shelf from 10 to 50 m (Robin et al, 2014;Costa et al, 2015). A short distance south (100 km), in the Cabo Frio upwelling region, Soares et al (2014) found similar δ 15 N values (higher than for other invertebrates of the present study) of loliginid species (D. plei -12.5‰ and D. sanpaulensis -11.0‰) compared with our results (13.3‰).…”
Section: Discussionmentioning
confidence: 99%
“…Prey selection is often proportional to prey availability in the environment (Link & Garrison, 2002), and preference for D . volitans could be attributed to its abundance in the study area, since it occurs at great densities along the shelf between 20–23°S (Costa et al ., 2015). Moreover, the protein content of D .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazilian waters, Argentine hake is considered a keystone species in the demersal community of the outer shelf and upper slope between 22–27°S (Nascimento et al ., 2012), as well as between 20–23°S (Costa et al ., 2015). Despite the importance of M. hubbsi in the demersal ecosystem, its trophic relationships have been poorly understood.…”
Section: Introductionmentioning
confidence: 99%